Do English Language Textbooks Represent Cultural Diversity? A Critical Discourse Analysis - Winda Sari; Joko Nurkamto; Ngadiso (Didaktika: Jurnal Kependidikan, 2025)
The representation of moral value in English language textbooks remains an underexplored issue, especially in relation to cultural diversity. This study investigated how moral values, as indicator of cultural diversity, was represented in junior high school English textbooks. Data were collected through documentation of the English for Nusantara Grade VIII textbook and supported by semi-structured interviews with three English teachers. The study employed Critical Discourse Analysis (CDA) based on Fairclough’s (2001) framework within a qualitative approach. Moral values were analyzed using six indicators proposed by Patel and Sharma (2021). The findings revealed that five of these indicators were present in the textbook, with responsibility being the most prominent. Other values such as honesty, fairness, compassion, and self-discipline appeared less frequently. Simplicity as the moral value also found in this study. The teachers emphasized the crucial role of integrating moral values to foster students' social behavior, including empathy, tolerance, respect, and collaboration. This study contributes to understanding how English textbooks promote cultural values and offers insights for enhancing the effectiveness of moral education in language learning.